Characterization and differential expression of DNA methyltransferase and demethylase genes in response to abiotic stress in Isodon rubescens - Xiaoxiao Zhang; Lili Zhu; Zihan Xu; Zhimin Wang; Liping Dai (BMC Plant Biology)
Abstract Background DNA methylation plays a key role in regulating plant growth and development, secondary metabolism, and environmental adaptability and is affected by DNA methyltransferase (C5-MTase) and demethylase (dMTase). However, the response of C5-MTase and dMTase genes to abiotic stress in Isodon rubescens remains largely unknown. Results In this study, eight IrC5-MTase genes and five IrdMTase genes were identified within the genome of I. rubescens. The IrC5-MTases were phylogenetically divided into four subfamilies (CMT, DRM, MET and DNMT2), and the IrdMTase were divided into two subgroups (ROS and DML) on the basis sequence similarity, conserved motif and domain architecture. The IrC5-MTase and IrdMTase genes were unevenly distributed on 5 and 4 chromosomes, respectively. Cis‑acting element analysis revealed that the IrC5-MTase and IrdMTase genes were enriched with multiple light-, phytohormone- and stress-responsive elements. Importantly, the level of DNA methylation in I. rubescens was influenced by different 5-azacytidine (5-azaC) concentrations or light intensities but unaffected by different NaCl concentrations. Accordingly, the expression of IrC5-MTase and IrdMTase genes were significantly upregulated or downregulated in response to different concentrations of 5-azaC or amounts of light stress, however, no conspicuous differences were observed under different degrees of NaCl stress. Expression correlation analysis revealed that the expression of IrCMT2a, IrMET1, and IrDML4 was most closely related to the DNA methylation level in I. rubescens. Conclusions Our results reveal the characteristics and differential expression of the IrC5-MTase and IrdMTase genes in response to 5-azaC, light or NaCl stresses and will facilitate future epigenetic studies in I. rubescens.